Soluble urokinase plasminogen activator receptor and its complicated role in hemodialysis (HD) patients with Covid-19 infection - Griveas, Ioannis; Schoinas, Antonios; Balitsari, Anthi; Asimakopoulos, Gerasimos; Pratilas, Evaggelos (Asian Journal of Medical Sciences, 2021)
Background: Soluble urokinase plasminogen receptor (suPAR) is a protein in the blood that has been described to reflect the severity status of systemic inflammation. Aims and Objective: We investigated the association between admission suPAR levels and severity and outcome of HD patients with Covid-19 infection. Materials and Methods: In an observational study of adult HD patients hospitalized for Covid-19, we measured suPAR levels in plasma samples. The time table for those measurements were as follows: at the beginning of admission, after hemoperfusion (HP) session for those patients that received them, and just before discharge. Results: Of the 17 patients (7 were male), 13 patients received HP (mean age: 74 years old). The median suPAR level was 12.94 ng/ml. For those who undertook HP in HD unit median suPAR level was before session 12.95 ng/mil and 6.2 ng/ml at the end of each session (p<0.05). 3 patients had suPAR level below 7 ng/ml. 2 of them survived without developing pleural effusions. 7 patients discharged from the hospital with median suPAR level 12.08 ng/ml which did not differ significantly from the median suPAR level of the diceased ones (13.68 ng/ml). Conclusion: Admission of suPAR levels in HD patients hospitalized for Covid-19 do not seem to be predictive for their clinical course in general. Chronic Kidney Disease and its relation to suPAR independently of patients’ inflammation status may be the key component for our notice. Despite that, in patients where low levels of suPAR combined with absence of pleural effusions the prognosis was excellent.